Anxiety Symptoms and Associated Factors among Outpatient Antenatal Mother: A Cross Sectional Study at University Malaya Medical Centre, Malaysia - AYU SULAINI, JUSOH; Haszalina, Hassan; Mardiana, M. (2014)
Introduction: Pregnancy is a time of great joy and excitement for many mothers to be, however it could also be stressful. It is a time when the mother becomes more vulnerable and this reduced level of control can add to the mother's perception of stress and anxiety. Emotional response can cause physical changes that can negatively affect the pregnancy. This study aims to evaluate the prevalence of anxiety symptoms and factors associated with anxiety among out-patient antenatal mother.Design: Cross-sectional study. Materials and Method: A cross sectional survey was conducted with 320 out-patient antenatal mothers from a major teaching hospital in Malaysia. Their anxiety symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS). Descriptive analysis and chi-square were used to evaluate the association between anxiety symptoms with socio-demographic factors, self-esteems and social supports. Result: This study revealed 35.5 % of the pregnant women experiencing significant anxiety symptoms at their first booking. Factors associated with significant anxiety symptoms among antenatal mother are the total family monthly income, mothers' period of gestations, history of obstetric complication and mothers' self-esteem. Conclusion: Anxiety symptoms are prevalent during pregnancy. Intervention to deal with the factors that increase the prevalence of anxiety at this stage is crucial to prevent the development of further psychological problems during pregnancy, delivery and post-delivery.